PENINGKATAN HASIL BELAJAR SEJARAH MELALUI PEMBELAJARAN DARING BERBASIS GOOGLE CLASSROOM (GC) PADA MASA PANDEMI COVID19 - Rosmaniar Rosmaniar (Jurnal Pendidikan Sang Surya, 2022)
This study aims to improve history learning activities through the application of Google Classroom (GC)-Based Online Learning for students during the Covid-19 Pandemic. This research was conducted with 25 students of class XII MIA1. By using the Kemmis and Mc. Taggart. The results of the observation showed that student activity increased from an average of 43.56 percent before the action to 68.9 percent in the first cycle, and became 81.9 percent at the end of the second cycle. student learning outcomes increased from an average of 67.2 before the action, to 72.6 in the first cycle and to 81.2 in the second cycle. Thus, it can be concluded that: the application of online learning based on google classroom in history learning can improve the activities and learning outcomes of XII MIA1 students at SMAN 7 Bulukumba in 2020/2021 (during the covid-19 pandemic).